Role of sarA in the Pathogenesis of Staphylococcus aureus Musculoskeletal Infection - Blevins, Jon S. (American Society for Microbiology, 2003)
We recently demonstrated that mutation of sarA in clinical isolates of Staphylococcus aureus results in a phenotype that is distinct by comparison to sarA mutants generated in the laboratory strain RN6390 (J. S. Blevins, K. E. Beenken, M. O. Elasri, B. K. Hurlburt, and M. S. Smeltzer, Infect. Immun. 70:470-480, 2002). This raises the possibility that studies demonstrating that RN6390 sarA mutants are attenuated do not accurately reflect the role of sarA in the pathogenesis of staphylococcal disease. To test this hypothesis, we used a murine model of musculoskeletal infection to assess the virulence of sarA and agr mutants generated in a clinical isolate of S. aureus (UAMS-1). By using this model, we confirmed that mutation of sarA and/or agr results in a reduced capacity to cause both septic arthritis and osteomyelitis.